2016
DOI: 10.1186/s12875-016-0541-9
|View full text |Cite
|
Sign up to set email alerts
|

Do primary care professionals agree about progress with implementation of primary care teams: results from a cross sectional study

Abstract: BackgroundPrimary care is the cornerstone of healthcare reform with policies across jurisdictions promoting interdisciplinary team working. The effective implementation of such health policies requires understanding the perspectives of all actors. However, there is a lack of research about health professionals’ views of this process. This study compares Primary Healthcare Professionals’ perceptions of the effectiveness of the Primary Care Strategy and Primary Care Team (PCT) implementation in Ireland.MethodsDe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Thomas et al [ 137 ] Sweden ENPT Healthy lifestyle promotion in primary care Process evaluation Mixed Retrospective Yes Yes Yes 100. Tierney et al [ 138 ] Ireland NPT Interdisciplinary teams in primary care Systematic review [ 194 196 ] Yes Process evaluation Quantitative Prospective Yes Yes No 101. Toye et al [ 139 ] Canada NPT Assessment instrument for homecare Yes Feasibility study Qualitative Prospective Yes Yes Yes 102.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomas et al [ 137 ] Sweden ENPT Healthy lifestyle promotion in primary care Process evaluation Mixed Retrospective Yes Yes Yes 100. Tierney et al [ 138 ] Ireland NPT Interdisciplinary teams in primary care Systematic review [ 194 196 ] Yes Process evaluation Quantitative Prospective Yes Yes No 101. Toye et al [ 139 ] Canada NPT Assessment instrument for homecare Yes Feasibility study Qualitative Prospective Yes Yes Yes 102.…”
Section: Resultsmentioning
confidence: 99%
“…This study raised important questions about how the interactions between clinicians’ (micro-level) experiences of the workability of complex interventions and meso-level organisational processes through which reflexive monitoring mechanisms play out their effects. Some studies were also explicitly concerned with implementing change in professional roles ( n = 7, 6.5% [ 20 , 54 , 63 , 70 , 94 , 101 , 138 ]). For example, Thomas et al [ 56 , 57 ] showed how changes in roles and workload interacted to promote the routine embedding of an intervention intended to manage incontinence in stroke patients.…”
Section: Resultsmentioning
confidence: 99%
“…Primary care team members in Ireland have previously reported valuing the structure and communication channels within their teams [37]. GP participation in primary care teams was considered particularly important for effective teamwork in a study surveying GPs and the wider multi-disciplinary team [38]. Geographical spread and multiple locations can be a barrier to effective communication in primary care [39,40].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Geographical spread and multiple locations can be a barrier to effective communication in primary care [39,40]. HCPs value co-location to facilitate face-to-face meetings between team members; however, GPs may not rate co-location as highly as other HCPs and in one recent study, GPs placed more emphasis on compensation for attendance at primary care meetings than other HCPs did [38]. It is important to note that GPs in the Irish primary care team system act independently, typically running their own practices as sole traders or partnerships, while the wider multi-disciplinary team members are health service employees.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Despite this, and other interim measures such as the national strategy for service user involvement, involvement of patients and communities in the development and running of PCTs is not routine practice across the country, is hard to achieve, and is generally not regarded by service providers as an important resource for PCTs . Therefore, the aforementioned gaps in international literature are also relevant to the Irish context…”
Section: Introductionmentioning
confidence: 99%